Investigating the Effect of Educational Interventions Based on the Health Belief Model on the Use of Personal Protective Equipment among the Workers of a Process Industry - farhad Forouharmajd; Seyed Mahdi Mousavi; mojtaba nakhaeipour; hossein ebrahimi (Muhandisī-i bihdāsht-i ḥirfah/ī)
Background and Objective: The present study sought to assess the effect of the Health Belief Model (HBM) on the use of Personal Protective equipment among the workers of a process industry. Materials and Methods: The study involved an experimental intervention with 100 workers from various units in a process industry. These employees were assigned to two groups of 50: intervention and control. Initially, data were gathered using a custom questionnaire based on the dimensions of the HBM. The intervention group underwent a 12-session educational program over 3 months. The post-test phase took place three months after the educational intervention. The data were analyzed using SPSS software (version 25). Results: The mean age scores of participants in intervention and control groups were 46±3 and 38± 2, respectively. The results indicated that following the educational intervention, the mean scores of awareness, perceived barriers, perceived benefits, and threats of employees were significantly higher than those of the control group (P<0.001), with respective scores of 15.45± 3.03, 22.21±2.30, 16.61±3.12. Conclusion: As evidenced by the obtained results, implementing educational interventions based on the HBM increased employees' awareness and favorable attitudes regarding using personal protective equipment.